PEMBERDAYAAN KADER PKK RW 04 KELURAHAN BADEAN KABUPATEN BONDOWOSO DALAM PENGOLAHAN JAHE SEBAGAI MINUMAN KESEHATAN - Indah Yulia Ningsih; Mochammad Amrun Hidayat; Ika Barokah Suryaningsih; Bambang Kuswandi (Jurnal Pengabdian kepada Masyarakat, 2026)
Ginger is a local plant with various health benefits. Currently, many processed ginger products are available on the market. However, the development of processed ginger products through innovative contemporary products such as ginger latte and ginger pink milk health drinks continues to increase community income. This community service program was carried out as an effort to improve the welfare of residents of RW 04, Badean Village, using the PRA (Participatory Rural Appraisal) method through counselling and training on processing ginger into health drinks because ginger is a local ingredient that is readily available at an affordable price in Bondowoso Regency. The significant role of kader PKK in the community is utilised as a motivating agent for women in their area to increase family income. The participants' enthusiasm for all activities is expected to be a widely beneficial solution for all residents as an alternative business to improve the family economy.